2021
DOI: 10.5430/jha.v10n2p45
|View full text |Cite
|
Sign up to set email alerts
|

Health uncertainty among healthcare workers during the COVID-19 pandemic

Abstract: Objective: Health uncertainty among healthcare workers has yet to be examined as a contributor to the psychological toll of the COVID-19 pandemic. We aimed to (1) characterize health uncertainty levels among healthcare workers in a large, U.S. hospital system during the COVID-19 pandemic and (2) examine associations between health uncertainty and psychological outcomes.Methods: From March to June 2020, healthcare workers in a large, urban U.S. healthcare system were invited to complete an online questionnaire.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For instance, one study reported that during the COVID-19 pandemic, healthcare workers with higher levels of health-related uncertainty suffered from more pronounced symptoms of anxiety, depression, and loneliness. 36 In addition, the COVID-19-related increase in the level of uncertainty stress has also been associated with poorer sleep status. 37 Although the above-presented evidence suggests that the COVID-19 pandemic is a major driver of uncertainty stress…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, one study reported that during the COVID-19 pandemic, healthcare workers with higher levels of health-related uncertainty suffered from more pronounced symptoms of anxiety, depression, and loneliness. 36 In addition, the COVID-19-related increase in the level of uncertainty stress has also been associated with poorer sleep status. 37 Although the above-presented evidence suggests that the COVID-19 pandemic is a major driver of uncertainty stress…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study reported that during the COVID-19 pandemic, healthcare workers with higher levels of health-related uncertainty suffered from more pronounced symptoms of anxiety, depression, and loneliness. 36 In addition, the COVID-19-related increase in the level of uncertainty stress has also been associated with poorer sleep status. 37 Although the above-presented evidence suggests that the COVID-19 pandemic is a major driver of uncertainty stress worsening physical and mental health, 1 , 6 , 36 , 37 future longitudinal studies assessing how uncertainty stress changes over time, accounting for potential future waves of COVID-19 spread, are needed to investigate this phenomenon in more detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation